Effects of low-volume, high-intensity training on performance in competitive swimmers: A systematic review - Nugent, F. J.; Comyns, T. M.; Burrows, E.; Warrington, G. D. (The Journal of Strength and Conditioning Research, 2017)
The purpose of this systematic review was to examine the extent and quality of the current research literature to determine the effects of low-volume, high-intensity training (HIT) on physiological performance and swimming performance in competitive swimmers. The methodology followed the preferred reporting items for systematic review and meta-analysis protocol. A search of relevant databases and conference proceedings was performed until December 2015. The inclusion criteria were (a) competitive swimmers, (b) =4 weeks HIT intervention, (c) comparison group had to involve a higher training volume, (d) outcome measures of physiological and swimming performance, and (e) all experimental study designs. Quality assessment was performed using the Quality Index checklist. Results indicate that of the 538 studies retrieved, 7 studies met the inclusion criteria. Six of the 7 studies found that an HIT intervention resulted in significant improvements in physiological performance. Four of the 7 studies found that HIT resulted in significant improvements in swimming performance, whereas none of the 7 studies resulted in a reduction in physiological or swimming performance. Despite the positive findings of this review, the short study duration is a limitation to a number of studies. The current evidence on the effects of HIT on performance is promising; however, it is difficult to draw accurate conclusions until further research has been conducted.